The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Oral Presentations 1981
DOI: 10.1055/s-0038-1652031
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Factor 4 (PF4) And β-Thromboglobulin (BTG) In Atherosclerosis And Diabetes Mellitus

Abstract: Distinguishing between in vitro and in vivo release of platelet specific proteins has led to problems in interpretation of clinical studies with PF4, and with BTG.As part of a prospective study of peripheral occlusive arterial disease in diabetes mellitus PF4 and BTG were measured together by specific radioimmunoassay in four groups of subjects age 50-70 years. Groups included (1) 106 normal subjects (NC); (2) 126 with clinical and objective evidence (transcutaneous doppler ultrasound and treadmill exercise) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…PF4 was increased in some studies in diabetics, especially in those with macroangiopathy, 115,197,198 whereas other investigators 113,190,196,199,200 found no difference between PF4 values of controls and diabetics with or without angiopathy.…”
Section: Platelet Factormentioning
confidence: 89%
See 1 more Smart Citation
“…PF4 was increased in some studies in diabetics, especially in those with macroangiopathy, 115,197,198 whereas other investigators 113,190,196,199,200 found no difference between PF4 values of controls and diabetics with or without angiopathy.…”
Section: Platelet Factormentioning
confidence: 89%
“…97 ' 115 ' 185 " 195 In patients with microangiopathy even higher BTG levels were observed. 97, 186,189,195,196 BTG levels were reduced 5 to 8 weeks after initiation of antidiabetic treatment in patients with recently detected diabetes. 97 No positive correlation was found between high BTG values in diabetics and Hb A1 .…”
Section: Beta-thromboglobulinmentioning
confidence: 93%